Evaluation of Prevalence of Low Back Pain Among Residents of Tabriz University of Medical Sciences in Relation with Their Position in Work - SHAMS VAHDATI, Samad (Turk J Emerg Med, 2016)
OBJECTIVES: Lower back pain is one of the most common complaints among the general population and among health professionals. Multiple workplace-related risk factors may contribute to back pain among physicians. The aim of this study was to assess the prevalence of lower back pain among medical residents of different medical specialties and to evaluate the relevant risk factors. METHODS: A Dutch Musculoskeletal Questionnaire (DMQ) was completed by 125 medical residents. Part I concerned general demographic information, part II evaluated workplace-specific factors, and part III assessed the individual characteristics of lower back pain. RESULTS: The overall prevalence of lower back pain among residents was 56.8%, with 45.1% of men and 76.5% of women reporting lower back pain. A total of 94.4% of affected individuals believed that their lower back pain was related to their current job, and 72.6% claimed that the onset of lower back pain occurred after beginning medical work. Statistical analysis revealed a significant correlation between lower back pain and certain risk factors, such as working in the same position for long periods, repetitive movement (bending, twisting) of the lumbar region, working in uncomfortable postures, stress, walking, and standing for long periods. However, no significant relationship was found between lower back pain and heavy lifting, smoking, or prolonged sitting. The role of exercise as a protective factor in reducing the incidence of lower back pain was supported by the statistical analysis. CONCLUSIONS: The prevalence of lower back pain among residents is high and is associated with a number of workplace-related risk factors.